HPV-Specific Systemic Antibody Responses and Memory B Cells are Independently Maintained up to 6 Years and in a Vaccine-Specific Manner Following Immunization with Cervarix and Gardasil in Adolescent and Young Adult Women in Vaccination Programs in Italy - Francesco Nicoli; Barbara Mantelli; Eleonora Gallerani; Valentina Telatin; Irene Bonazzi; Peggy Marconi; Riccardo Gavioli; Liliana Gabrielli; Tiziana Lazzarotto; Luisa Barzon; Giorgio Palù; Antonella Caputo (Vaccines, 2020)
Human papillomavirus (HPV) persistent infections are associated with cervical cancer and other HPV-related diseases and tumors. Thus, the characterization of long lasting immunity to currently available HPV vaccines is important. A total of 149 female subjects vaccinated with Cervarix or Gardasil participated to the study and they were stratified according to age (10−12-year-old and 16−20-year-old). Humoral immune responses (IgG and neutralizing antibody titers, antibody avidity) and circulating memory B cells were analyzed after an average of 4−6 years from the third immunization. The humoral responses against HPV-16 and HPV-18 (and HPV-6 and HPV-11 for Gardasil) were high in both age groups and vaccines up to six years from the third dose. However, Cervarix induced significantly higher and more persistent antibody responses, while the two vaccines were rather equivalent in inducing memory B cells against HPV-16 and HPV-18. Moreover, the percentage of subjects with vaccine-specific memory B cells was even superior among Gardasil vaccinees and, conversely, Cervarix vaccinated individuals with circulating antibodies, but undetectable memory B cells were found. Finally, a higher proportion of Cervarix-vaccinated subjects displayed cross-neutralizing responses against non-vaccine types HPV-31 and HPV-45. Gardasil and Cervarix may, thus, differently affect long-lasting humoral immunity from both the quantitative and qualitative point of view.